Kontroversi Zakat Profesi - L.Man, Yovenska (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2016)
The development of Fiqh issues is in line with the development of the times, as the phenomenon that occurs today. Various kinds of problems that occur cause the scholars are required to provide solutions to solutions to these problems one of the problems of zakat which until now has not been maximized so that makes contemporary scholars make a breakthrough by issuing a Fatwa on Zakat Profession. Nevertheless, this opinion still gets the pros and cons of most Ulama.Keyword: Controversy, Zakat Profession